Northeastern Kalimantan hydroclimate of Core SO217-18522 over 50 kyrs - Marfasran Hendrizan; Wolfgang Kuhnt; Ann E Holbourn; Sri Yudawati Cahyarini; Nining Sari Ningsih (PANGAEA, 2025)
Changes in convective activity and hydroclimate over Northeastern Kalimantan are key features to understand glacial to interglacial climate evolution in the center of the West Pacific Warm Pool during the Late Pleistocene to Holocene. We use high-resolution X-ray fluorescence (XRF)-scanner derived elemental ratios in sediment Core SO217-18522 (1 24.106 extquotesingle N, 119 4.701 extquotesingleE, 975 m water depth) recovered from the northern Makassar Strait to reconstruct changes in precipitation-related weathering and erosion over Northeastern Kalimantan over the last 50 kyr. Enhanced seasonality of rainfall and an extended dry season during Heinrich Stadials (HS4 to HS1) and the Younger Dryas (YD) suggest weakening of the tropical convection associated with a southward shift of the tropical rain belt and the annual mean position of the Intertropical Tropical Convection Zone. Increasing sediment discharge and intensification of convective activity occurred during the early to mid-Holocene during an interval of high Northern Hemisphere insolation, elevated atmospheric pCO2 levels and global warming. Our reconstructions in comparison with regional terrestrial and marine records highlight the high spatial variability of Kalimantan hydroclimate on millennial to glacial-interglacial timescales.